Formation au portfolio dans un ENT : analyse de l'activité dans le dispositif hybride et effets sur l'apprentissage - Christian Michaud (Centre National d'Enseignement à Distance, 2013)
This research is focused on the curriculum implemented in order to involve students in master's degree (towards teaching careers) in a portfolio process. The consequences of the implementation in a digital work environment are pointed out. The portfolio didactic sequence has to be adapted before being used in a technical and pedagogical device such as Spiral Connect. This article reports the uses by the students when they create their own electronic portfolio in a digital work environment and analyzes the effects and tensions on learning. The methodology is based on several data: connections with the platform Spiral Connect, types of activities, questionnaires and students' productions.